The ROX@PDA@PCL vascularized bionic nerve conduit facilitates the restoration of nerve defects - Lin, Daoyi; Peng, Jun; Zhang, Yichong; Wang, Xiaoping; Xu, Xiaodong; Jia, Jing (Frontiers in Neurology, 2025)
Previous research has highlighted the pivotal role of angiogenesis in facilitating nerve function repair following nerve injury. In this study, we employed polydopamine (PDA) to modify polycaprolactone (PCL) and subsequently loaded it with roxadustat (ROX), thereby constructing a vascularized nerve conduit for the repair of a 10 mm sciatic nerve defect in rats. At 2 weeks post-surgery, new blood vessels were evaluated by immunofluorescence staining. Twelve weeks post-surgery, a comprehensive suite of assessments was conducted to evaluate the efficacy of the conduit, including gait analysis, determination of gastrocnemius muscle wet weight recovery, electrophysiological examination of gastrocnemius compound action potential (CMAP), Masson staining to evaluate gastrocnemius muscle fiber cross-sectional area, toluidine blue staining to assess the total number of regenerated myelinated nerve fibers, and electron microscopic observation of myelin sheath thickness. Our findings revealed that ROX@PDA@PCL could promote the proliferation of vascular endothelial cells and significantly enhance angiogenesis in regenerated nerves (p < 0.05). Regarding the recovery of neurological function, compared to the PDA@PCL and PCL groups, the ROX@PDA@PCL group exhibited significantly superior outcomes in the sciatic functional index (SFI), CMAP, gastrocnemius muscle wet weight ratio, muscle fiber cross-sectional area, total number of regenerated myelinated nerve fibers, and myelin sheath thickness. These indices approached those of the autologous group, but were still lower than in the autograft group (p < 0.05). The study underscores the potential of the vascularized nerve graft (ROX@PDA@PCL), constructed through PDA-mediated loading of ROX onto PCL, to enhance functional nerve recovery. Our findings present a promising new therapeutic approach for the clinical repair of peripheral nerve defects.